Yeti claws: Cheliped sexual dimorphism and symmetry in deep-sea yeti crabs (Kiwaidae) - Christopher Nicolai Roterman; Molly McArthur; Cecilia Laverty Baralle; Leigh Marsh; Jon T. Copley (PLoS ONE, 2025)
Yeti crabs (Kiwaidae) are deep-sea hydrothermal vent and methane seep dwelling crustaceans that farm chemosynthetic microbes on their bodies. Sexual dimorphism is a common feature of decapod crustaceans, but little is known about its prevalence in species from deep-sea habitats. We address this knowledge deficit by investigating claw sexual dimorphism and symmetry in the hydrothermal-vent endemic ’Hoff crab’, Kiwa tyleri. A total of 135 specimens from the East Scotia Ridge were examined, revealing mean asymmetry indices close to zero with respect to propodus length and height, albeit with a significantly larger number of marginally left-dominant individuals with respect to propodus length, possibly indicative of some task specialisation between claws, or a vestigial ancestral trait. Both male and female claws exhibit positive allometry with increasing carapace length, but males possess significantly larger claws compared with females when accounting for carapace size, exhibiting faster growing propodus length, and broader propodus heights throughout the size distribution. This marked difference is indicative of either male-male competition for mate access, sexual selection, or differential energy allocation (growth vs reproduction) between males and females, as observed in other decapod crustaceans. In contrast, a reanalysis of data for the methane seep inhabiting yeti crab Kiwa puravida revealed no significant difference in claw allometry, indicating a possible lack of similar sexual selection pressures, and highlighting potential key differences in the ecological and reproductive strategies of K. tyleri and K. puravida relating to claw function, microbial productivity and population density. Whether sex differences in claw allometry represents the norm or the exception in Kiwaidae will require the examination of other species in the family. This research enhances our understanding of the behaviour, ecology and evolution of yeti crabs, providing a basis for future studies.